Wind driven current profile in the presence of different boundaries - Chen, Ching-yu; Suphat Vongvisessomjai; Prida Thimakorn; Gupta, Ashim Das; Ret-Ser Engineering Agency (R.O.C.) (Bangkok : Asian Institute of Technology, 1979)
The wind induced flow phenomena especially the surface drift currents in a closed basin are investigated. The laboratory experiments of such phenomena have been made under various wind velocities and different boundary conditions. The measurements include the wind profiles over the water surface, the drift current profile, the characteristics of waves. The general shape of drift current profiles was changed with various wind velo city and different boundary conditions. The point of zero drift currents on an average is 20 percent of the total depth bel ow water surface in spite of various wind velocities under different boundary conditions. The logarithmic distribution of drift current profile holds for both downwind and reversed direction but not continuously. The mean water surface set-up variation is a main role controlling return flow. The research will be useful for the understanding of movement of oil slicks and transports of pollutants.
A thesis submitted in partial fulfillment of requirements for the degree of master of engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1980
Keywords: Ocean currents